Effect of Supplemental Humate at Different Levels on the Growth Performance, Slaughter and Carcass Traits of Broilers - Karaoglu, Mevlut; Macit, Muhlis; Esenbuga, Nurinisa; Durdag, Hulya; Bilgin, O. Cevdet; Turgut, Leyla (International Journal of Poultry Science, 2004)
The current trial was carried out to determine the influence of supplemental humates including humic, fulvic and ulmic acids and some microminerals on the performance and carcass traits of broilers. A study was conducted with total 240 male broiler chicks (Ross-308), received from a commercial hatchery at 1 day of age. Chicks were allocated to four dietary treatments (H0, H1, H2 and H3 groups) as completely randomized experimental design . Feed and water were offered for ad libitum consumption and lightening was continuous throughout experimental period. A basal diet (H0), basal diet plus 0.10 (H1), 0.20 (H2) and 0.30 % (H3) humate (Farmagulator DRYTM, Humate, Farmavet International Inc., Kocaeli 41400, Turkey) were offered during experimental period. All birds were housed in batteries from 1 to 21 days, and in grower broiler pens to 49 days in the Application and Research Farm of the Agricultural Faculty, Ataturk University. At the end of the trial all birds were slaughtered. Feed intake and body weight gains were recorded weekly per pen. Final body weights were 2525, 2494, 2646 and 2546 g for H0, H1, H2 and H3 groups respectively, and the difference was not significant. Average daily weight gains were 51.8, 49.8, 52.9 and 49.9 g, respectively, and the supplementation had statistically no significant effect on this parameter. Daily feed consumptions were 103.2, 95.6, 104.4 and 98.6 g and the difference between control and treatment groups was significant (P